Innovation & intellectual property : collaborative dynamics in Africa - Armstrong, C (Chris), 1965-; De Beer, Jeremy, 1975-; Oguamanam, Chidi, 1965-; Schonwetter, Tobias (Published by UCT Press in association with the IP Unit, Faculty of Law, University of Cape Town and Deutsche Gesellschaft für Internationale, 2014)
The Open African Innovation Research and Training (Open A.I.R.) project focused on the intersection of innovation, intellectual property (IP), and development in Africa and this book offers its research findings. Its case studies cover nine African countries--Egypt, Nigeria, Ghana, Ethiopia, Uganda, Kenya, Mozambique, Botswana, and South Africa--looking at IP rights in a range of sites of innovation: agricultural production, biofuel technology, traditional medicine, research collaboration, automotive manufacturing, music production, and scholarly publishing.